Transmembrane oligomeric intermediates of pore forming toxin Cytolysin A determine leakage kinetics. Issue 82 (7th November 2017) - Agrawal, Ayush; Apoorva, K.; Ayappa, K. G.
Abstract : Leakage kinetics of Cytolysin A, an α pore forming toxin, occurs through stochastic insertion of oligomeric intermediates or 'arcs'. Abstract : Calcein leakage experiments for the α pore forming toxin Cytolysin A (ClyA) are carried out using a suspension of small unilamellar vesicles made up of 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) and cholesterol. Combining the oligomerization kinetics with a Poisson process to describe the inherent stochasticity underlying pore formation, we screen possible oligomerization pathways by comparing model predictions with calcein leakage data for ClyA. Excellent agreement with the leakage data was obtained for a reversible sequential oligomerization mechanism upon inclusion of leakage from membrane inserted partially oligomerized intermediates or 'arcs'. In contrast, the non-sequential mechanisms were unable to predict the calcein leakage data. Reversibility in the oligomerization mechanism maintains a constant supply of protomers resulting in a broad distribution of oligomers at steady state. Additionally, the time scale for the conformational change from the water soluble monomer to the membrane bound protomer was found to be similar or larger than the time scale for oligomerization. The dominant contribution to leakage was found to occur from the smaller arcs, consistent with the low protein to lipid ratios used in the experiment. Our kinetic model is able to capture both the fast and slow time constants typically observed in calcein leakage experiments. A key inference is that arcs play a critical role in the leakage kinetics of ClyA, with the fast leakage time scale arising from the smaller oligomerized intermediates and the longer time scale arising from the slowly forming higher order oligomers.